PRELIMINARY DOCUMENTATION AT INTERVENTIONS OF BUILT HERITAGE. CASE ANALYSIS: THE CHURCH OF SAN FRANCISCO DE LIMA (1978-1990) - Alcántara Gómez, Rosa María (2018)
The article analyzes a document of the final report produced by the United Nations Educational, Scientific and Cultural Organization (UNESCO) on an intervention carried out in the complex of the Church of San Francisco between 1978 and 1990. Nonetheless, since said document has more financial than technical information, it was necessary to draw on sources, because the purpose of the article is to demonstrate the importance of prior documentation in the interventions of built heritage. Their analysis allows one to know the background of the property, crucial for the elaboration of a future conservation proposal. In the first place, we seek to give a general overview of the country’s context: we explain the political, social and economic context in Peru at the time the property was intervened, as well as the territorial conditions of Lima and its seismic history. Also, we seek to understand the concept of restoration had at the time, and detail the role of the main actors in this project, UNESCO and the National Institute of Culture (INC), in order to, then analyze the document, the Final Report of the National Project UNDP/UNESCO, projects PER/77/007 and PER/89/009. Thus, we highlight the importance of previous and subsequent documentation for intervention on a property through the analysis of the case study.